A case of mandible Paget's disease of the bone treated with intravenous neridronate - A. Fassio; L. Idolazzi; M. Rossini; O. Viapiana; D. Gatti (PAGEPress Publications, 2016)
Paget's disease of bone (PDB) is a focal disorder of osteoclasts, leading to chaotic bone remodelling, and it is characterized by the presence of focal areas of excessive bone formation alongside with areas of focal bone resorption. The typical radiographic feature is the cotton wool appearance. To date, bisphosphonates are the mainstay of the treatment. We hereby report the case of a young woman presenting with mandible PDB, with a relevant diagnostic delay and mistakenly treated for five years with chronic oral corticosteroids. After our evaluation, the patient received treatment with intravenous neridronate (an amino-bisphosphonate licensed in Italy for the treatment of this disease), with achievement of clinical remission.